Analysis of Service Strategy in Increasing Customer Satisfaction at Indonesia Islamic Bank - Ahmad Fauzul Hakim Hasibuan; M. Reihan; Dwi Thirta Andrean; Aisah Bela Citra (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
In recent years, Islamic banking in Indonesia has shown positive developments as shown by the increasing number of Islamic banks in Indonesia. To increase its market share, Islamic banking needs to analyze what factors influence the public to be willing to become customers at Islamic banks, one of which is through service quality. This study aims to examine the effect of service quality on customer satisfaction at Bank Syariah Indonesia. The research method used in this study is using data collection methods. The data collection method used is library research, library research. Methods of data collection in the library, reading, recording and managing research materials. The type of data used is qualitative data.